Effects of early pregnancy on NOD-like receptor expression in the ovine endometrium - Zhang, Leying; Cai, Jiabao; Wang, Xinxin; Yang, Zhen; Ding, Haiquan; Yang, Ling (Frontiers in Veterinary Science, 2024)
Introduction Nucleotide-binding domain (NOD)-like receptors (NLRs) are expressed in the endometrium, and involved in modulating the female innate immune responses. There are conceptus-endometrial interactions during pregnancy, which ensure immune homeostasis of the maternal-fetal interface. The purpose of this study was to explore the effects of early pregnancy on NLR expression in the ovine endometrium. Methods Endometrial tissues were collected at day 16 of the estrous cycle, and at days 13, 16 and 25 of pregnancy (n = 6 for each group), and RT-qPCR, western blot and immunohistochemistry analysis were used to analyze the expression of NLRs, including NOD1, NOD2, major histocompatibility complex class II transactivator (CIITA), neuronal apoptosis inhibitor protein (NAIP), NLR family, pyrin domain-containing 1 (NLRP1), NLRP3 and NLRP7. Results Expression levels of NOD1, NOD2, NAIP, CIITA, NLRP1 and NLRP3 declined, but expression level of NLRP7 increased in the endometria during early pregnancy compared with nonpregnant ewes. In addition, NOD2 and CIITA proteins were located in the endometrium in a protein type-, cell type- and pregnancy status-specific manner. Discussion Early pregnancy modulated expression of NLR family in the ovine endometrium, which may be essential for conceptus-endometrial interactions and maternal-fetal interface immune homeostasis.